Problematika Pola Asuh Orangtua Pasca Perceraian Terhadap Keberhasilan Pendidikan Agama Islam Remaja Di Pati Pada Era Society 5.0: The Challenges of Post-Divorce Parenting and Its Influence on the Islamic Religious Education Success of Adolescents in Pati During the Society 5.0 EraThe Challenges of Post-Divorce Parenting and Its Influence on the Islamic Religious Education Success of Adolescents in Pati During the Society 5.0 Era - Indah Ayu Mayasari; Muhammad Miftah (Educan, 2025)
This study aims to analyze the problematic parenting patterns after divorce on the success of Islamic Religious Education for adolescents in the Society 5.0 era, by highlighting the importance of collaboration between parents and Islamic Religious Education (PAI) teachers. The research method used is a qualitative approach with a case study type. Data collection techniques include in-depth interviews, observation, and documentation of adolescents, parents, and PAI teachers. The study was conducted in Pegandan Village, Margorejo District, Pati Regency, on April 8–30, 2025. Pati Regency was chosen because it is one of the areas with the highest divorce rates in Central Java. The data were analyzed descriptively qualitatively to describe the dynamics of post-divorce parenting patterns and the influence of parent-teacher collaboration on the success of adolescent religious education. The results of the study show that the success of adolescent Islamic Religious Education is not only influenced by parental parenting patterns, but also by the level of effective collaboration between parents and PAI teachers. Collaboration that is established in the form of intensive communication, agreement in instilling religious values, and emotional and academic support has been shown to strengthen the achievement of adolescent Islamic Religious Education, even in separated family conditions. This finding confirms the importance of synergy between the family and school environments in fostering adolescent spiritual resilience amidst the challenges of the Society 5.0 era.